OPTIMALISASI STRATEGIS UMKM BATIK TULIS MALANGAN SEBAGAI UPAYA MENJAGA DAN MELESTARIKAN BUDAYA LUHUR BATIK, PADA BATIK TULIS NIATI KOTA MALANG - Aditya Pramana; Cindy Pramita; Agus Hermawan (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
Batik Niati, an MSME specializing in Malangan Batik Tulis, plays a crucial role in the preservation of Indonesia's cultural heritage. Through a comprehensive community service program, they are committed to becoming pioneers among Batik Tulis MSMEs in Malang City. The program consists of four main activities: (1) Socialization and the creation of MSME SOPs, (2) Training on effectively uploading and managing Instagram accounts, (3) Assistance in creating simple financial bookkeeping for MSMEs, and (4) Assistance in building brand image. By implementing this program, Batik Niati aims to achieve significant development in the future. The hope is that through the maintenance of batik traditions, these MSMEs will not only create high-quality products but also act as agents of change in supporting the sustainability of local cultural heritage. With well-aligned SOPs, effective online presence, organized financial bookkeeping, and a strong brand image, Batik Niati is expected to become an inspiring role model for other Batik Tulis MSMEs in Malang City, creating a broader positive impact on the development of the MSME sector and cultural preservation.